A rare case of Brooke-Spiegler syndrome - Anuja Sunkwad; Sunanda Mahajan; Jayati Dave; Dhanjit Kumar Das (Wolters Kluwer Medknow Publications, 2020)
Brooke-Spiegler syndrome (BSS) is a rare autosomal dominant inherited disorder characterized by multiple skin appendageal tumors. The predominant tumors can be a cylindroma, trichoepithelioma, and/or spiradenoma. Here we report this rare entity of Brooke-Spiegler syndrome in a 50 year old female on the basis of clinico-histopathological correlation. The gene responsible for this condition is cylindromatosis gene (CYLD1) which has been mapped on chromosome 16q12-q13. However, no mutation have been detected in CYLD gene analyzed in our patient which indicates lack of genotype-phenotype correlation in this patient.